2020
DOI: 10.3390/ijms21134789
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green Loaded Modified Mesoporous Silica Nanoparticles as an Effective Photothermal Nanoplatform

Abstract: Photothermal therapy possesses great advantages for the treatment of drug-resistant tumors. Herein, Near Infrared (NIR)-triggered photothermal nanoparticles were developed through loading indocyanine green (ICG), a kind of NIR dye, into amino group-modified silica nanoparticles (SiO2-NH2 NPs). SiO2-NH2 NPs were prepared with immobilization of the amino groups into the framework of silica nanoparticles (SiO2 NPs) by employing (3-aminopropyl)-triethoxysilane (APTES). Before and after the modification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The red shift towards longer wavelengths is indicative of changes in the physiochemical environment, likely attributed to polaric-π* transitions resulting from electrostatic interactions between ICG molecules and the nanoparticles. 61 The florescent intensity of the ICG/BPs based on total concentration was determined using the NIR window (840 nm). Using a starting sample of 5 mg of ICG/BPs resuspended into Milli-Q water, 100uL aliquots that would equate to 40, 20, 15, 10, and 5 μM ICG (assuming a 100% loading efficiency) were measured out.…”
Section: Resultsmentioning
confidence: 99%
“…The red shift towards longer wavelengths is indicative of changes in the physiochemical environment, likely attributed to polaric-π* transitions resulting from electrostatic interactions between ICG molecules and the nanoparticles. 61 The florescent intensity of the ICG/BPs based on total concentration was determined using the NIR window (840 nm). Using a starting sample of 5 mg of ICG/BPs resuspended into Milli-Q water, 100uL aliquots that would equate to 40, 20, 15, 10, and 5 μM ICG (assuming a 100% loading efficiency) were measured out.…”
Section: Resultsmentioning
confidence: 99%
“…After surface coating of ICG, these SiO 2 -NH 2 @ICG NPs absorption in NIR-spectra progresses widely. This study revealed that these NPs exhibit significant killing of tumor cells [34]. Miranda et al illustrated that the straightforward combination of indocyanine green (ICG) with liposomes containing DOTAP (1,2-dioleoyl-3-tri-methyl-ammonium-propane) leads to complete binding of ICG to the liposomes, thereby augmenting the optical properties of ICG.…”
Section: Indocyanine Green (Icg)mentioning
confidence: 97%
“…Mesoporous silica nanoparticles are the most efficient drug delivery agent used for the codelivery of PA and chemotherapeutics in combination therapy [66]. Wang et al developed NIR-triggered photothermal nanoparticles incorporating indocyanine green into amino-group-modified silica nanoparticles [67]. They have successfully demonstrated that the synthesized photothermal nanoparticles have the potential for enhanced cancer cell killings.…”
Section: Photothermal Therapymentioning
confidence: 99%